Acute Alcohol Intake Affects Internal Additive Noise and the Perceptual Template in Visual Perception - Zhang, Pan; Guo, Yeshuo; Qiao, Yuxin; Yan, Nan; Zhang, Yajing; Ren, Weicong; Zhang, Shilei; Wu, Di (Frontiers in Neuroscience, 2022)
A reduction in visual performance is among the serious consequences of acute alcohol intake. Contrast sensitivity (CS) is a fundamental feature of visual function. Here, we investigated the negative effect of a moderate dose of alcohol on CS across a wide range of spatial frequencies and with multiple levels of external noise and clarified the corresponding mechanisms in the context of a perceptual template model (PTM). To avoid the effect of alcohol washout, a quick contrast sensitivity function (qCSF) method was used to assess the visual performance of subjects before and 30 min after a moderate dose of alcohol intake. We found that (1) CS was significantly disrupted by acute alcohol intake; (2) alcohol-induced CS loss was dependent on spatial frequency and external noise; and (3) increased internal additive noise and an impaired perceptual template accounted for alcohol-induced CS loss. These results help us better understand the negative effect of alcohol consumption and provide guidance for driver safety studies.